Dataset of breakthrough time for various modified sand materials using Rhodamine-B as an adsorbate - Pratik Kumar; Satinder Kaur Brar; Maximiliano Cledon; Azadeh Kermanshahi-pour; Rosa Galvez-Cloutier (Data in Brief, 2019)
Removal of synthetic dyes from wastewater generated by the textile industries is important. Rhodamine-B is widely used colorant and is medically proven to lead to tissue borne sarcoma, reproductive and neurotoxicity issues in humans, if still present in the treated drinking water. Herein, this dataset provides information on different forms of sand materials for their effective utilization as an adsorbent material for Rhodamine-B. The effectiveness of the media was measured in terms of breakthrough time obtained. One of the 27 presented data set is a part of a research article [1] explaining the breakthrough time of these filter media under specific experimental condition. All these data is a combination of three variables that were studied: a) concentration of Rhodamine-B (1 mg/L, 5 mg/L and 10 mg/L), b) flow velocity of Rhodamine-B spiked water (2 mL/min, 5 mL/min and 10 mL/min) and c) bed height (7.5 cm, 10 cm, and 12.5 cm). At any bed height, the breakthrough time of graphitized sand (brewery sugar coated, GS1) was found to be 3–4 times higher than the second best adsorbent, i.e., manganese dioxide coated on GS1. Keywords: Rhodamine-B, Sand media, Graphitized sand, Manganese-coated sand, Adsorption, Breakthrough time